Answer:
x = - 5, x = - 1
Explanation:
Given
- 3 | 2x + 6 | = - 12 ( divide both sides by - 3 )
| 2x + 6 | = 4
The absolute value always returns a positive value, but the expression inside can be positive or negative, that is
2x + 6 = 4 ( subtract 6 from both sides )
2x = - 2 ( divide both sides by 2 )
x = - 1
OR
- (2x + 6) = 4 ← distribute left side
- 2x - 6 = 4 ( add 6 to both sides )
- 2x = 10 ( divide both sides by - 2 )
x = - 5
As a check
Substitute these values into the left side of the equation and if equal to the right side then they are the solutions.
x = - 1 → - 3| - 2 + 6 | = - 3 | 4 | = - 3 × 4 = - 12 ← True
x = - 5 → - 3 | - 10 + 6 | = - 3 | - 4 | = - 3 × 4 = - 12 ← True
Thus x = - 5 and x = - 1 are the solutions